Healthcare Professionals’ Retirement Intentions: The Roles of Financial and Work Factors - YETTY SHOBO 3674528; Jen D Wong (Journal of Financial Therapy, 2019)
Delayed retirement has been utilized to provide short-term solution to the healthcare workforce demand-supply gap arising from increased retirement and healthcare needs by aging population. To adequately design an effective financial therapy and retirement delaying program, a knowledge of key factors affecting retirement intentions is critical. This study examines the influences of financial and work-related factors on retirement intentions among a sample of 21,860 healthcare professionals between 50 to 65 years old. Using data from the Virginia’s 2016 Dentist, Licensed Practical Nurse, Registered Nurse, Physician, and Pharmacist Surveys, multinomial logistic regressions were used to identify key factors associated with retirement intentions. Study findings showed that having lower income, education debt, and higher job satisfaction, among other factors, were associated with delayed retirement intentions. Incorporating this finding will be key in the creation of successful retirement delaying programs and ultimately in the reduction of the healthcare workforce demand-supply gap.
Keywords: Financial Factors; Work Factors; Healthcare Professionals; Retirement Intentions; Job Satisfaction; Education Debt